2018
DOI: 10.4102/aveh.v77i1.434
|View full text |Cite
|
Sign up to set email alerts
|

Professional collaboration for vision and healthcare in Cameroon

Abstract: Collaboration in healthcare is evident when healthcare professionals communicate well with each other, assume complementary roles to cooperatively work together and share responsibility for problem-solving and decisionmaking to formulate and carry out plans for patient or client care. Specific collaborative activities include sharing of information, discussion of complicated cases, and referrals to colleagues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In light of this, it is recommended that actors in the fi eld should devise ways of increasing awareness of existing rehabilitation and related organisations in the NW Region, and that organisations continue to be established and supported. This knowledge is important for referrals and improved services yet is challenging in this practice context (Okwen et al, 2018). An inventory of organisations is not currently available but should be created for consultation.…”
Section: Discussionmentioning
confidence: 99%
“…In light of this, it is recommended that actors in the fi eld should devise ways of increasing awareness of existing rehabilitation and related organisations in the NW Region, and that organisations continue to be established and supported. This knowledge is important for referrals and improved services yet is challenging in this practice context (Okwen et al, 2018). An inventory of organisations is not currently available but should be created for consultation.…”
Section: Discussionmentioning
confidence: 99%
“…According to a research done, there are lots of benefits in collaborating in healthcare and shows evidences that support that building collaborative work among HCPs has shown an improvement in patient care and safety outcomes, helps to improve skills and knowledge of professionals, reinforces good and effective communication, leading to continuous development in decision making which leads to better and more cost-effective healthcare systems which are beneficial for patients (Kwen, Signe, MacPella, Mbibeh, & Cockburn, 2018). Researches done by several authors have discovered that studies done in various contexts to find out the impact on PS has identified reductions in the rates of medical errors when IPC is strong and teams are trained to work efficiently, cooperatively and safely (Brandis, 2017;Busan, Moll, & Duits, 2017;Zúñiga, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Lasker, Weiss, and Miller (2001), Green and Johnson (2015) contend that collaboration is highly effective in achieving health outcomes. Nonetheless, collaboration has a high potential to fail when leadership challenges are present (Bauer, AbouAssi, and Johnston 2020) and resources are minimal, as is the case in many parts of Africa (Okwen et al 2018). The process of exploring collaboration in many African contexts can be frustratingly slow and ineffective due to the aforementioned barriers.…”
Section: Introductionmentioning
confidence: 99%